2012
DOI: 10.1002/14651858.cd004544.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Banding ligation versus beta-blockers for primary prevention in oesophageal varices in adults

Abstract: This review found a beneficial effect of banding ligation on primary prevention of upper gastrointestinal bleeding in patient with oesophageal varices. The effect on bleeding did not reduce mortality. Additional evidence is needed to determine whether our results reflect that non-selective beta-blockers have other beneficial effects than on bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 88 publications
5
95
1
10
Order By: Relevance
“…A Cochrane review of 19 RCTs published in 2012 demonstrated that EVL was associated with significantly lower rates of both upper gastrointestinal bleeding (14 vs. 20%) and AVB (13 vs. 19%), although the beneficial effect of EVL was not confirmed in a sub-group analysis of trials with adequate randomisation or fully published studies. In addition, no difference in mortality was noted between the EVL and NSBB groups [18].…”
Section: Prophylaxis With Endoscopic Variceal Ligation (Evl)mentioning
confidence: 84%
“…A Cochrane review of 19 RCTs published in 2012 demonstrated that EVL was associated with significantly lower rates of both upper gastrointestinal bleeding (14 vs. 20%) and AVB (13 vs. 19%), although the beneficial effect of EVL was not confirmed in a sub-group analysis of trials with adequate randomisation or fully published studies. In addition, no difference in mortality was noted between the EVL and NSBB groups [18].…”
Section: Prophylaxis With Endoscopic Variceal Ligation (Evl)mentioning
confidence: 84%
“…Elastic band ligation of haemorrhoids was developed by Barron in 1963 [1] and is now a well-established treatment methodology. Banding of oesophageal varies in both emergency and elective contexts are also an important intervention [2]. Elastic bands have even been utilised as an alternative to umbilical cord clamping [3].…”
Section: Discussionmentioning
confidence: 99%
“…1), with no differences seen in bleeding-related mortality [29,30]. The strength of the conclusion that EBL is superior to NSBB is, however, significantly limited by the quality of the trials included in the analysis.…”
Section: Clinical Scenarios For the Treatment Of Portal Hypertensionmentioning
confidence: 99%